2024
DOI: 10.1088/1402-4896/ad1ea9
|View full text |Cite
|
Sign up to set email alerts
|

Correlated noise enhances performance of joint remote state preparation in quantum multi-hop network

Zhihua Zhang,
Hanchen Zhang,
Beining Shen
et al.

Abstract: Joint remote state preparation (JRSP for short)can increase the security of quantum communication by distributing different parts of classical information to different senders. However, the communication efficiency in terms of fidelity decreases with the increase of intermediate nodes in multi-hop network. In this paper, we try to explore methods to improve fidelity of JRSP in multi-hop network presented by Zhang and Chen in 2023 Phys. Scr. 98 065107. Specifically, correlated Pauli noise with partial memory was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 77 publications
0
0
0
Order By: Relevance
“…QE is an essential and important resource in quantum science and technology [1]. QE is the key ingredient of various quantum information processing tasks such as quantum teleportation [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18], remote state preparation [19][20][21][22][23][24], superdense coding [25][26][27], quantum state sharing [28][29][30], quantum key distribution [31][32][33][34] and quantum secure direct communication [35][36][37] etc Generally, the entangled state used as the quantum channels is generated by exploiting the same degrees of freedom of two or more quantum systems. However, it has been reported that the capacity of quantum communication schemes can be enhanced by exploiting multiple degrees of freedom for the generation of entanglement, called hyperentanglement [38,39], between two or more quantum systems.…”
Section: Introductionmentioning
confidence: 99%
“…QE is an essential and important resource in quantum science and technology [1]. QE is the key ingredient of various quantum information processing tasks such as quantum teleportation [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18], remote state preparation [19][20][21][22][23][24], superdense coding [25][26][27], quantum state sharing [28][29][30], quantum key distribution [31][32][33][34] and quantum secure direct communication [35][36][37] etc Generally, the entangled state used as the quantum channels is generated by exploiting the same degrees of freedom of two or more quantum systems. However, it has been reported that the capacity of quantum communication schemes can be enhanced by exploiting multiple degrees of freedom for the generation of entanglement, called hyperentanglement [38,39], between two or more quantum systems.…”
Section: Introductionmentioning
confidence: 99%